Ultrasonic Nondestructive Testing Method for Mechanical Properties of Metallic Nanomaterials. Issue 5 (January 2021) - Li, Jiabing; Zhong, Rui; Shen, Xingwang; Gao, Ziyun; Zhang, Junwei; Miao, Hansen; Zhang, Ziqian
Abstract: For metallic nanomaterials, the small size scale of nanoparticles leads to a significant increase in their surface area, resulting in a series of new mechanical properties. In order to detect the mechanical properties of metal nanomaterials, a new ultrasonic nondestructive testing method is proposed. Using defocusing measurement and time discrimination method, the surface wave velocity of metal nanomaterials at different positions and angles was measured, and the mechanical properties at corresponding positions and angles were obtained. The experimental results show that the new ultrasonic nondestructive testing method can accurately characterize the mechanical properties of metal nanomaterials without causing damage to the tested objects.